An Assessment of Flood Hazard in Nigeria: The Case of Mile 12, Lagos - Olajuyigbe, A. E; Rotowa, O.O; Durojaye, E. (Richtmann Publishing, 2012)
Apart from traffic congestion, flood is the most common serious physical urban problem in most Nigerian cities. Thisusually results from high river levels, concentration of overland flow following heavy rainfall, limited capacity of drainage systemsand blockage of waterways and drainage channels. This study identified the factors responsible for perennial flooding in Mile 12area of Lagos, Nigeria which has constituted serious menace in terms of socio-economic and environmental consequences. Theresearch methodology involved questionnaire administration on households, key informant interview especially on Lagos StatePhysical Development Authority (LASPPDA) officials and participant-observation, while other data were collected fromsecondary sources including various relevant publications and text books. The result shows that the perennial flooding problemin Mile 12 is as a result of consistent high rainfall and water releases from Oyan dam in the neighbouring state of Ogun, Nigeria.Other causes of flood in the study area include blockage of drainage channels by refuse and other wastes, narrow river channelsand construction along floodplain. In a bid to ameliorate the seemingly intractable problem of flooding in the study area, therecommendations made include: provision of sufficient setback to streams and rivers, construction of roads with good drainagesystem, channelization and building of more dams to avoid excess loading of the existing dam.